Pathologic findings in 48 dogs exposed to nonaccidental trauma (physical abuse) in the central region of Rio Grande do Sul, Brazil - Ramos, C. P.; Fighera, R. A.; Flores, M. M. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
Over the last years, the human society has been demonstrating an increasing interest in the prosecution of crimes against animals (LOCKWOOD, 2006). As a consequence of the growing connection and dependence between humans and animals, the laws regarding animal abuse have become more specific and rigid (FARACO, 2008). Based on this fact, the number of studies concerning post mortem findings in cases of animal abuse have increased over the years. The aim of this study was to analyze the post mortem findings in all canine necropsy cases confirmed as “nonaccidental trauma” at the Laboratório de Patologia Veterinária from the Universidade Federal de Santa Maria (LPV-UFSM) from 1964 to 2016.